Burn injuries related to E-cigarettes reported to poison control centers in the United States, 2010-2019 - Baoguang Wang; Sherry T. Liu; Brian Rostron; Camille Hayslett (BMC, 2020)
Abstract Background United States (U.S.) national data indicate that 2035 individuals with burn injuries from e-cigarette explosions presented to U.S. hospital emergency departments (EDs) in 2015-2017. This national estimate is valuable for understanding the burden of burn injuries from e-cigarette explosions among individuals who presented to EDs. However, little is known about individuals who experienced e-cigarette-related burns but may not present to EDs or health care facilities. Findings We analyzed data from the National Poison Data System (NPDS) to describe frequency and characteristics of e-cigarette-related burn cases in the U.S. in 2010-2019. NPDS contains information collected during telephone calls to poison control centers (PCCs) across the U.S., including e-cigarette-related burns and other unintended events. During 2010-2019, 19,306 exposure cases involving e-cigarettes were documented in NPDS. Of those, 69 were burn cases. The number of burn cases increased from one in 2011 to a peak of 26 in 2016, then decreased to three in 2019. The majority of the burn cases occurred among young adults aged 18-24 years (29.0%; n = 20) and adults aged 25 years or older (43.5%; n = 30); 14.4% (n = 10) occurred among individuals ≤17 years old. Of the 69 burn cases, 5.8% (n = 4) were admitted to a hospital; 65.2% (n = 45) were treated and released; 15.9% (n = 11) were not referred to a health care facility (HCF); 4.4% (n = 3) refused referral or did not arrive at an HCF; and 8.7% (n = 6) were lost to follow-up or left the HCF against medical advice. Nearly one-third (30.4%; n = 21) of the cases had a minor effect (symptoms resolved quickly), 47.8% (n = 33) had a moderate effect (symptoms were more pronounced and prolonged than in minor cases, but not life-threatening), and 2.9% (n = 2) had a major effect (life-threatening symptoms). Conclusions Approximately one-fifth of e-cigarette-related burn cases reported to PCCs were not referred to or did not arrive at an HCF. Some burn cases had serious medical outcomes. The burn cases mostly affected young adults and adults aged 25 years or older. The number of burn cases in NPDS represents a small portion of e-cigarette-related burn cases but it can serve as a complementary data source to traditional injury surveillance systems.